1993
DOI: 10.1093/jmedent/30.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multiple Blood Feeding in Aedes aegypti (Diptera: Culicidae) During a Single Gonotrophic Cycle Using a Histologic Technique

Abstract: We evaluated a histologic technique for its usefulness in detecting multiple blood feeding by Aedes aegypti (L.) in a single gonotrophic cycle. To standardize the procedure, we carried out a laboratory study in which 166 mosquitoes imbibed two blood meals at known intervals. Eighty percent (78/98) of the multiple meals were detected when the interval between meals was from 1 to < to = 24 h and the time from the second meal to fixation ranged from 0 to 12 hr. At intervals outside this range, only 34% (23/68) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
1
6

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 0 publications
2
124
1
6
Order By: Relevance
“…1 A and Boreham et al 1979, Burkot et al 1988) but also in Ae. aegypti (Macdonald 1956, Sheppard et al 1969, Scott et. al 1993.…”
Section: Resultsmentioning
confidence: 99%
“…1 A and Boreham et al 1979, Burkot et al 1988) but also in Ae. aegypti (Macdonald 1956, Sheppard et al 1969, Scott et. al 1993.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 This day-biting mosquito has a close association with the urban environment, 3,4 almost exclusively feeding on human hosts 5,6 and breeding in artificial containers found in the domestic setting (i.e., pot plant bases, tires, roof gutters, etc.). 7 Aedes aegypti regularly take multiple blood meals, often from different humans, to complete their gonotrophic cycle.…”
Section: Introductionmentioning
confidence: 99%
“…7 Aedes aegypti regularly take multiple blood meals, often from different humans, to complete their gonotrophic cycle. 6 Multiple blood feeding is epidemiologically important because it increases the probability of a mosquito contracting or transmitting a virus infection, often leading to clusters of dengue virus infections to occur in time and space (i.e., family and neighboring units). 5 It is therefore imperative that during a dengue outbreak people infected with the virus and their closest neighbors take precautions to prevent vectors biting to interrupt the virus transmission cycle.…”
Section: Introductionmentioning
confidence: 99%
“…A. aegypti infected with dengue viruses may temporarily be transported by air or ship into Japan and the US and survive during the summer, with the possibility of domestic transmission by A. albopictus. These mosquitoes normally feed on a single vertebrate host, but a small percentage of each of the 2 species feed on more than 1 host during 1 gonotrophic cycle 21 and that multiple-feeding behavior is of epidemiological significance. Despite the fact that the vectors can travel up to 2.5 km daily in an open environment, a study in Africa found that only 0.7% of mosquitoes visited more than 4 houses.…”
Section: Discussionmentioning
confidence: 99%